Promoting appropriate utilisation of laboratory tests for inflammation at an academic medical centre. Issue 1 (24th February 2020) - Bartlett, Kristen J; Vo, Ann P; Rueckert, Justin; Wojewoda, Christina; Steckel, Elizabeth H; Stinnett-Donnelly, Justin; Repp, Allen B
Abstract : Erythrocyte sedimentation rate (ESR) and C reactive protein (CRP) are commonly ordered in clinical practice to evaluate for inflammation. CRP is a more sensitive and specific test for detecting acute phase inflammation, and the American Society for Clinical Pathology recommends ordering CRP rather than ESR to detect acute phase inflammation in patients with undiagnosed conditions. We sought to understand CRP and ESR ordering practices and reduce unnecessary use of ESR testing at our academic medical centre. We surveyed physician leaders in clinical areas with high utilisation of ESR testing to understand the drivers of potential overutilisation of these tests. Based on survey responses, we designed an intervention focused on education, clinical decision support within the electronic medical record and quarterly audit and feedback. We evaluated appropriateness of ESR ordering before and after the intervention via structured chart audit. Comparison of monthly rates of ESR tests during the preintervention and postintervention periods was conducted using interrupted time series analysis. Clinical habit and ease of test ordering were identified as key drivers of ESR overuse. Compared with the preintervention period, we observed a 33% reduction in the number of ESR tests per month and a 25% reduction in combined CRP and ESR tests per month during the postintervention period. This reduction corresponded to an annual avoidance of 2633 ESR tests with a corresponding estimated direct cost avoidance of $23 701 annually. Although the rate of ESR testing decreased, there was no significant improvement in the clinical appropriateness of residual ESR test ordering following the intervention. A multifaceted intervention was associated with significant decreases in unnecessary ESR tests and concurrent ESR and CRP tests at our academic medical centre. Despite these reductions, there are continued opportunities to reduce inappropriate ESR testing.